2012
DOI: 10.1007/s11356-012-0829-9
|View full text |Cite
|
Sign up to set email alerts
|

Optimization of artificial neural network models through genetic algorithms for surface ozone concentration forecasting

Abstract: In the prediction of O(3) concentrations, the threshold model that considers two regimes was the one that fitted the data most efficiently.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

0
19
0

Year Published

2012
2012
2020
2020

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 20 publications
(19 citation statements)
references
References 42 publications
0
19
0
Order By: Relevance
“…One of the most applied statistical models is the artificial neural network (ANN). ANNs are nonlinear models, which are inspired in the biological neural processing system [24,25]. These models are composed by artificial neurons (grouped in layers; three layers-input, hidden, and output-are often applied) that receive an input value and converts to an output through a selected function (activation function).…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…One of the most applied statistical models is the artificial neural network (ANN). ANNs are nonlinear models, which are inspired in the biological neural processing system [24,25]. These models are composed by artificial neurons (grouped in layers; three layers-input, hidden, and output-are often applied) that receive an input value and converts to an output through a selected function (activation function).…”
Section: Introductionmentioning
confidence: 99%
“…In recent studies, O 3 concentrations have shown different behaviors regarding certain explanatory variables [25,37], which can be classified as O 3 regimes. This observation can be justified by the chemical reactions associated with O 3 formation/destruction that are influenced by certain variables, such as temperature, solar radiation, and wind speed [32].…”
Section: Introductionmentioning
confidence: 99%
“…Several studies have applied ANNs to forecast and predict the concentration of one or more air pollutants in an area, as well as its effects on the human health consequences (Gardner & Dorling, 1998;Grivas & Chaloulakou, 2006;, Pires 2012. In the present study, three types of two-layer back propagation ANNs with different training algorithms, LLR and DLLR, were applied for data modeling.…”
Section: Discussionmentioning
confidence: 99%
“…Three types of feed-forward ANNS were applied to predict O3 with 8 inputs (CO, NO2, O3, T, RH, and WS). In this study, the GA was used in order to search the numberof neurons and activation functions in hidden layers (Pires 2012). .…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation